Poor and rich in James : a relevance theory approach to James's use of the Old Testament - Morales, Nelson R. (University Park, Pennsylvania : Eisenbrauns, 2018)
"Employing Relevance Theory as a methodological framework, examines how the book of James uses the Old Testament in passages on wealth and poverty"--Provided by publisher.
Includes bibliographical references (pages 241-265) and index.
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Relation to the Old Testament; Poverty -- Biblical teaching; Wealth -- Biblical teaching